A Review on Therapeutic Potential of Plumbago zeylanica Extracts and Sustainable Production Methods - Tripathi, Chetana; Jain, Sachin Kumar; Vengurlekar, Sudha (Anti-Infective Agents, 2025)
Herbal medicines have earned a timeless place in healthcare, valued for their biocompatibility and widespread use in treating cancer and related conditions. Plumbago zeylanica, widely recognized as white leadwort or doctorbush, holds a prominent place in traditional medicine systems worldwide, revered for its diverse therapeutic properties. This widespread use, however, coupled with unsustainable harvesting practices, has raised concerns about the plant's long-term survival in its natural habitat. Their enduring presence is particularly evident in countries like India, Pakistan, Bangladesh, Sri Lanka, and Australia, where they are deeply rooted in ethnomedical traditions. P. zeylanica stands out as a rich source of bioactive compounds, including naphthoquinones, flavonoids, alkaloids, and terpenoids, with plumbagin identified as a key driver of its medicinal properties. Plumbagin exhibits a remarkable pharmacological profile, demonstrating significant efficacy as an anticancer, antidiabetic, antimalarial, and antimicrobial agent, making it a promising candidate for drug development. The literature reveals that the root and root bark also have a wider claim in traditional medicines against various diseases as a memory enhancer, anti-inflammatory, wound healing, anti-infertility, blood coagulation, and anti-oxidant activities. This review provides a comprehensive overview of P. zeylanica, encompassing its traditional uses, phytochemical composition, and the pharmacological activities of its key bioactive constituents, with a particular focus on plumbagin. We delve into the scientific evidence supporting its therapeutic applications, highlighting its potential in treating a wide range of diseases. Furthermore, we discuss the progress made in developing sustainable production methods for plumbagin for medicinal purposes from P. zeylanica.
Keywords: Plumbago zeylanica